2017
DOI: 10.1002/ejhf.931
|View full text |Cite
|
Sign up to set email alerts
|

Volume load‐induced right ventricular dysfunction in animal models: insights in a translational gap in congenital heart disease

Abstract: 809 Hedges' g (95% CI) 0.2 (-1.0-1.5) Study Regurgitation models (n=135): P=0.737, I2=90.6% ) COMBINED (n=280): P=0.005, I2=86.7% 0 -7,5 7,5 Hedges' g (95% CI) 4.Study Regurgitation models (n=109): P<0.001, I2=61.0% Shunt models (n=81): P<0.001, I2=88.2% Ruzicka 1993, 7d (n=16) Ruzicka 1993, 28d (n=16) Szabó 2006, 90d (n=18) Bartelds 2011, 30d (n=11) Borgdorff 2012, 28d (n=20) COMBINED (n=190): P<0.001, I2=84.8%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Zebrafish embryos are excellent for non-invasive live imaging, but their small size and clutch numbers make systematic proteomic analysis difficult. The data and conclusions obtained from different animal models can be mutually confirmed and complement each other, and jointly construct a panoramic view of understanding of heart development and cardiovascular diseases ( Afouda and Hoppler, 2009 ; Bossers et al, 2018 ).…”
Section: Heart Development Is Highly Conserved Across Speciesmentioning
confidence: 69%
See 1 more Smart Citation
“…Zebrafish embryos are excellent for non-invasive live imaging, but their small size and clutch numbers make systematic proteomic analysis difficult. The data and conclusions obtained from different animal models can be mutually confirmed and complement each other, and jointly construct a panoramic view of understanding of heart development and cardiovascular diseases ( Afouda and Hoppler, 2009 ; Bossers et al, 2018 ).…”
Section: Heart Development Is Highly Conserved Across Speciesmentioning
confidence: 69%
“…Zebrafish possess highly efficient cardiac regenerative capacity throughout their lifetime, providing novel insights into the understanding of human cardiac regeneration ( Bournele and Beis, 2016 ; Bossers et al, 2018 ). The zebrafish heart can reform a fully functional heart even after substantial damages ( Sehring et al, 2016 ; Tahara et al, 2016 ; González-Rosa et al, 2018 ).…”
Section: Heart Regeneration In Non-mammalian Organisms and Applicatiomentioning
confidence: 99%
“…Chronic PR results in abnormal increase in RV preload and afterload, and over time leads to irreversible RV dysfunction and cardiovascular morbidities. [3][4][5] The current study showed that echocardiographic indices of RV-PA coupling were comparable to CMRI-derived RV…”
Section: Discussionmentioning
confidence: 82%
“…Chronic pulmonary regurgitation (PR), which is one of the most common reasons for reintervention in adults with congenital heart disease, particularly in patients with tetralogy of Fallot (TOF) and valvular pulmonic stenosis (VPS) with prior right ventricular (RV) outflow tract interventions . Chronic PR causes RV volume overload resulting in increased RV preload, as well as volume overload of the proximal central pulmonary artery (PA) and vascular remodeling ultimately resulting in increased RV afterload . The goal of pulmonary valve replacement is to prevent progressive RV dysfunction by normalizing these abnormal loading conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation